Application of diagram methods and hierarchical agglomerative procedures to assess the risk of investment funds on The Warsaw Stock Exchange - Homa, Magdalena; Mościbrodzka, Monika (Zastosowanie metod diagramowych i hierarchicznych procedur aglomeracyjnych w analizie ryzyka funduszy inwestycyjnych na GPW w Warszawie, 2016)
The issue of the article focuses on the need for the selection of investment funds of the Warsaw Stock Exchange with a certain similarity in terms of investment risk. For this purpose, the selected hierarchical agglomeration procedures and the diagrams methods that allowed creating a map of the funds, describing their diversity and diversity of the market, were applied. In addition, the compatibility of the obtained results were verified in terms of the measures of the investment risks designated by the fund managers
Nauki o Finansach = Financial Sciences, 2016, Nr 4 (29), s. 21-34
Keywords: fundusze inwestycyjne; diagram methods; hierarchical agglomerative procedures; investment funds; metody diagramowe; hierarchiczne proceduty aglomeracyjne